Organelle genome assembly, annotation, and comparative analyses of Typha latifolia and T. domingensis: two keystone species for wetlands worldwide - Soe, Thida; Kong, Jiali; Nie, Liyun; Wang, Jie; Peng, Dan; Tembrock, Luke R.; Wu, Zhiqiang (Frontiers in Plant Science, 2024)
Typha is a cosmopolitan aquatic plant genus that includes species with widespread global distributions. In previous studies, a revised molecular phylogeny was inferred using seven plastid loci from nine Typha species across different geographic regions.By utilizing complete organellar genomes, we aim to provide a more comprehensive dataset that offers a robust phylogenetic signal for resolving Typha species evolutionary relationships. Here, we assembled T. latifolia and T. domingensis mitochondrial genomes (mitogenomes) using a combination of short-read and long-read data (PacBio, ONT). we present the complete assembly and annotation of the organellar genomes of two common Typha species, T. latifolia and T. domingensis.The mitogenomes mitochondrial genomes (mitogenomes) of both species are assembled into single circular molecules of 395,136 bp and 395,140 bp in length, respectively, with a similar GC content of 46.7%. A total of 39 protein-coding genes, 17 tRNA genes, and 3 rRNA genes were annotated in both mitogenomes. The plastid genomes (plastomes) of both species possess typical quadripartite structures observed across most plants, with sizes of 161,545 bp and 161,230 bp. The overall average GC content of the plastomes of both species was 36.6%. The comparative analysis of the plastome and mitogenome revealed that 12 mitogenome DNA fragments share similar sequences with in the repeat regions of the corresponding plastomes, suggesting a past transfer of repeat regions into the mitogenome. Additionally, the mitogenomes of the two Typha species exhibited high sequence conservation with several syntenic blocks.Phylogenetic analysis of the organellar genomes of the two Typha species and 10 related species produced congruent phylogenetic trees. The availability of these organellar genomes from two Typha species provide valuable genetic resources for studying the evolution of Typhaceae and will improve taxonomic classifications within the family.